IMPLIKASI FIKIH MADZHAB TERHADAP PELAKSANAAN IBADAH DI PESANTREN YASRIB KAB. SOPPENG - MUCHSIN, AGUS; MUCHSIN, AGUS (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
Religious traditions in the wake of the Pesantren Yasrib actually not much different from other boarding schools. The procedure for the implementation of worship performed in a boarding school environment grounded in the tradition of worship of the chaplain. Book reference boarding study by the chaplain, among others, Kifayat al Akhyar, Tanwir al Qulub, Fath al Muâin, Iâanah al Thalibin, and Fath al Qarib, by their Shaf âand Syafâiyah. Implementation of worship in boarding schools embrace the dominant Yasrib Shafâi fqh schools, it is shown in the procedures for conducting such as ablution and prayer worship them. However Yasrib Islamic Boarding School also still moderate in sect because there are some other worship implementation that are not found in the reference Shaf and Shaf, among others; wudoo thing for people who when skin contact with the opposite sex is considered as an emergency, but Shaf âonly tolerate for three days. The rest is beyond the capacity of the emergency. Similarly, in the distribution of alms and the type of plants that must pay zakat as well as claims against the bank interest is not based entirely on Shaf schools